Identifikasi Perilaku Pengunjung Pengguna Ruang Publik Taman Indonesia Kaya, Kota Semarang - Napitupulu, Cindy Barry; Wungo, Grandy Loranessa (Teknik PWK (Perencanaan Wilayah Kota), 2024)
Public space in general has a definition as an element of the built and natural environment, public and private, external and internal, rural and urban, where visitors have freedom and access that has no boundaries. The formation of the uniqueness of public space is based on the relationship between the built environment and human behavior patterns. Behavior refers to the reaction or response to the impulse that affects it. A person's way of behaving cannot be equalized because a person's response will be different to the impulses that affect him. The existence of Taman Indonesia Kaya as an open public space is an important element in order to create a city space that is fun, livable and attractive to urban people. The phenomenon in Taman Indonesia Kaya in relation to the built environment with humans is conflicts between space users based on age groups. The purpose of this research is to identify visitor behavior in using Taman Indonesia Kaya. The research method used in this study is to use quantitative methods, as well as the analysis used, namely descriptive statistical analysis and Behaviour Mapping analysis. The results obtained from this research resulted in the characteristics of visitors with adolescent age groups and the dominance of jogging and sitting on the ground behavior.